EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME REGARDING THE MANAGEMENT AND PREVENTION OF AVIAN FLU (H5N1) AMONG ADULTS AGED (30-50 YEARS) - UMA. E, THIRISHA.K; P, VAISHNUDEVI.; J, VARSHA.; P, KALPANA. (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The rising non-communicable disease burden, the persistent threat of infectious disease outbreaks and an increased risk of violence and injuries are key public health concerns in urban areas.The population that the intervention is intended to study and take conclusions from is known as the target population. A target population, also referred to as a target audience, is a group of people with particular characteristics that may be effectively defined to distinguish them from the general population.Research gap refers to an area or topic within a field of study that has not yet been extensively researched or is yet to be explored. It is a question, problem or issue that has not been addressed or resolved by previous research.